Content of essential oil of fennel seeds in two different stages of development - De Figueiredo, Roseane O. [UNESP] (My University, 2002)
This experiment was carried out at Plant Production Sector, Agronomical Science College-Botucatu, S.P., Brazil, in March, 2000. The aim of this assay was to determine the yield of essential oil of fennel (Foeniculum vulgare Miller) in different stages of development. Essential oils were prepared by hydrodistillation from the seeds using of Clevenger apparatus. The water utilized for the extraction of essential oil was sufficient to cover 100 g of seeds and the mixture was distilled for three hours. The volume of essential oil in the graduated side -arm of Clevenger apparatus was observed. There were no significative difference statistic was observed (Tukey 5%) in percentage (v/m) of oil content, based on dry weight of green seeds compared with dry weight of mature seeds, when they were harvested in two different stages of development. There was significative difference statistic between data obtained of humidity content of green seeds when these were compared with mature seeds. These results shows that others specifics studies about adaptation of fennel in tropical conditions are necessary, because the obtained data were different of data described on literature.
Keywords: Apiaceae; Foeniculum vulgare Miller; Green seeds; Hydrodistillation; Mature seeds; Medicinal plants